1963
DOI: 10.1002/hlca.19630460419
|View full text |Cite
|
Sign up to set email alerts
|

Über die Isolierung neuer Stoffwechselprodukte aus Penicillium brefeldianum DODGE

Abstract: ZUSAMMENFASSUNG 1235 4,5,6-Trimethoxy-N, N-dimethyl-tryptamin (XI) und zwei dem Mescalin nahestehende Verbindungen, fi-(3,4,5-Trimethoxyphenoxy)-athyl-amin (VI) und ,4,5-Trimethoxyphenoxy)-athyl-dimethylamin (III), wurden synthetisiert. Keine der drei Substanzen zeigte in vorlaufigen Humanversuchen psychotrope Aktivitat. Vor etwa 28 Jahren haben OXFORD et ~1 .~) aus dem Kulturfiltrat von Penicillium brefeldianum DODGE die Fulvinsaure (I) z, 3, isoliert. Der gleiche Pilz produziert auch Grise~fulvin~). Bei der … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0
3

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(56 citation statements)
references
References 13 publications
2
51
0
3
Order By: Relevance
“…lactone (18). Phenotypes such as endomembrane bodies (P1 and P2), apparent cytoplasmic localization (P8), or vacuolar body formation (P12), were displayed for the examined markers in different combinations (SI Appendix, Fig.…”
Section: High-content Cellular Screen For Molecules Affects the Recycmentioning
confidence: 99%
“…lactone (18). Phenotypes such as endomembrane bodies (P1 and P2), apparent cytoplasmic localization (P8), or vacuolar body formation (P12), were displayed for the examined markers in different combinations (SI Appendix, Fig.…”
Section: High-content Cellular Screen For Molecules Affects the Recycmentioning
confidence: 99%
“…1 In an early study of this compound, the (6S)-chirality, trans-junction between the two rings and the E-stereochemistry of the conjugated double bond were established. 3 The solid-state stereochemical features of 1 were obtained from an x-ray crystallographic study. 4 Weber et al 4 also noted that the antiperiplanar (ca 180°) relationships found for H(1)-C(1)-C(14a)-H(14a) and H(11)-C(11)-C(11a)-H(11a) in the solid-state were also retained in CDCl 3 solution, as indicated by their vicinal coupling constants of ca 9 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of ARF GEP have been distinguished by their susceptibility to inhibition by brefeldin A (BFA), a macrocyclic lactone synthesized from palmitate by a variety of fungi (15) and initially identified as an antiviral agent (16). After it was found that BFA inhibits an early step in secretion causing retention of secretory and membrane proteins in the ER of many cells (17), it became an important tool for the study of intracellular vesicular trafficking.…”
mentioning
confidence: 99%